2018
DOI: 10.1158/1078-0432.ccr-17-0345
|View full text |Cite
|
Sign up to set email alerts
|

Honokiol Radiosensitizes Squamous Cell Carcinoma of the Head and Neck by Downregulation of Survivin

Abstract: Purpose Previous studies revealed diverging results regarding the role of survivin in squamous cell carcinoma of the head and neck (SCCHN).This study aimed to evaluate the clinical significance of survivin expression in SCCHN; the function of survivin in DNA damage repair following ionizing radiationtherapy (RT) in SCCHN cells; and the potential of honokiol to enhance RT through downregulation of survivin. Experimental Design Expression of survivin in SCCHN patient primary tumor tissues (n=100) was analyzed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 47 publications
(61 reference statements)
2
13
1
Order By: Relevance
“…Furthermore, reduction of survivin expression by Brexpiprazole sensitizes glioma cells to osimertinib treatment (33). In addition, suppression of survivin promotes the tumor-killing effect of radiotherapy in prostate cancer (34) and head and neck squamous cell carcinoma (HNSCC) (35,36). In the present study, we found that survivin is highly expressed in OSCC Recent studies showed that the ubiquitin-proteasome pathway induces survivin degradation in a cell cycle-dependent manner (10).…”
Section: Discussionsupporting
confidence: 55%
“…Furthermore, reduction of survivin expression by Brexpiprazole sensitizes glioma cells to osimertinib treatment (33). In addition, suppression of survivin promotes the tumor-killing effect of radiotherapy in prostate cancer (34) and head and neck squamous cell carcinoma (HNSCC) (35,36). In the present study, we found that survivin is highly expressed in OSCC Recent studies showed that the ubiquitin-proteasome pathway induces survivin degradation in a cell cycle-dependent manner (10).…”
Section: Discussionsupporting
confidence: 55%
“…Similar effect was observed in oral cancer cells where honokiol suppressed JAK2/STAT3 activation and, inhibited IL-6-mediated cell migration [95,183]. Furthermore, another study indicated that honokiol induces apoptosis in human glioblastoma cell line U87 through suppressing the phosphorylation of STAT3 (Tyr705), down-regulating survivin, and upregulating cleaved caspase-3 expression [98].…”
Section: Signal Transducers and Activators Of Transcription (Stats)supporting
confidence: 55%
“…The increasing ratio of proapoptotic to antiapoptotic Bcl-2 family proteins (Bax/Bcl-2) will induce the release of cytochrome c and other apoptogenic proteins through the mitochondrial membrane to the cytosol, subsequently leading to the activation of caspase cascade and apoptosis [34]. Furthermore, honokiol downregulated the expression of several other anti-apoptosis mRNA and proteins such as Bcl-xL [13,18,25,64], survivin [67,98], and MCL-1 [18], as well as upregulated other pro-apoptotic proteins such as BAD, BAX, and BAK proteins [18,25].…”
Section: Dual Induction Of Apoptotic and Necrotic Cell Deathmentioning
confidence: 99%
“…Furthermore, reduction of survivin expression by Brexpiprazole sensitizes glioma cells to osimertinib treatment [33]. In addition, suppression of survivin promotes the tumorkilling effect of radiotherapy in prostate cancer [34] and head and neck squamous cell carcinoma (HNSCC) [35,36]. In the present study, we found that survivin is highly expressed in OSCC tumor tissues and cells, depletion of survivin expression by sgRNA blunted the malignant phenotypes in OSCC cells, including in vitro cell proliferation, colony formation, and in vivo tumor development.…”
Section: Discussionmentioning
confidence: 99%